Ambivalent entrepreneurs: arts-based social enterprise in a neoliberal world. Issue 2 (30th March 2020) - McQuilten, Grace; Warr, Deborah; Humphery, Kim; Spiers, Amy
Abstract : Purpose: The purpose of this paper is to consider the social turn in contemporary capitalism and contemporary art through the lens of art-based social enterprises (ASEs) that aim to create positive social benefits for young people experiencing forms of marginalisation, and which trade creative products or services to help fulfil that mission. A growth in ASEs demonstrates a growing interest in how the arts can support social and economic development, and the ways new economic models can generate employment for individuals excluded from the labour market; extend opportunities for more people to participate in art markets; and challenge dominant market models of cultural production and consumption. Design/methodology/approach: This paper considers a number of challenges and complexities faced by ASEs that embrace a co-dependence of three goals, which are often in tension and competition – artistic practice, social purpose and economic activity. It does so by analysing interviews from staff working with 12 ASE organisation's across Australia. Findings: While the external forces that shape ASEs – including government policy, markets, investors and philanthropy – are interested in the "self-sufficient" economic potential of ASEs, those working in ASEs tend to prioritise social values and ethical business over large financial returns and are often ambivalent about their roles as entrepreneurs. This ambivalence is symptomatic of a position that is simultaneously critical and affirmative, of the conditions of contemporary capitalism and neoliberalism. Originality/value: This paper addresses a gap in social enterprise literature presenting empirical research focussing on the lived experience of those managing and leading ASEs in Australia.